Religion and Spirituality of Elderly Living in a Geriatrics Ward - Meneses Duarte, Flávia (2011)
This study evaluated the influence of religion and spirituality on the way in which elderly patients cope with their hospitalization. A total of 30 elderly living in a geriatrics ward participated in the study. The instruments used were: a socio-demographic questionnaire and the DUREL Religious Scale (Duke Religious Index). Results indicate that the elderly attach much importance to their spiritual and religious beliefs to cope with their hospitalization. Recognizing the well-being that these aspects provide for the elderly is to provide humanized care. In order to do that, the development of further research and evaluation tools on the theme is suggested, as well as the inclusion of disciplines of religion and spirituality in the training of health professionals.